Zeolite minerals from the North Shore of the Minas Basin, Nova Scotia - Pe-Piper, Georgia; Miller, Lisa (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 2003)
ABSTRACT X-ray diffraction and electron microprobe analyses show the following assemblages to be present in basalt flows and overlying siliciclastic sedimentary rocks along the North Shore of the Minas Basin: Five Islands — chabazite and stilbite are dominant, also "heulandite" and barrerite; Two Islands — analcime is dominant, gmelinite, chabazite, stilbite, and natrolite; Wasson Bluff — chabazite, stilbite and "heulandite" are dominant, also herschelite, barrerite, stellerite, analcime, wairakite, natrolite, clinoptilolite, and thomsonite; Partridge Island — chabazite and stilbite are dominant, also analcime, epistilbite, natrolite, barrerite, and "heulandite"; Cape Sharp — chabazite, stilbite, barrerite, stellerite, and "heulandite"; Horseshoe Cove — "heulandite" and stilbite; Western Cape d'Or — analcime, stilbite, natrolite, and mesolite are dominant, also stellerite, ?epistilbite, barrerite, scolecite, chabazite, "heulandite", wairakite, tetranatrolite and laumontite. Comparison is made with assemblages at Arlington Quarry on North Mountain, where the dominant zeolite minerals are heulandite (sensu stricto) and stilbite. Elsewhere on North Mountain, mordenite, natrolite, and laumontite have been confirmed. Chemical composition of hydrothermal fluids was likely different between North Mountain and the North Shore, with fluids in the latter area less sodic. The temperature of zeolite crystallization appears to have been high at Arlington Quarry, where "heulandite" and stilbite crystallised with little Na in their crystal structure. With falling temperature the crystallizing solution became enriched in Na, and sodic zeolite minerals, such as natrolite, began to crystallize. At lower temperatures on the North Shore, Na was accommodated in the structure of chabazite and other zeolites such as analcime, and final crystallisation was represented by only small amounts of Na-rich zeolites (natrolite group). At Wasson Bluff, basalt flows of the North Mountain Basalt and overlying siliciclastic sediments of the McCoy Brook Formation are all dismembered by synchronous movement on the nearby left-lateral Portapique Fault. The dominant vesicle fillings in basalt are celadonite and silica minerals, with minor "heulandite", chabazite, and analcime. The oldest basaltic clasts in the McCoy Brook Formation contain a similar mineral assemblage (including sparse "heulandite" and chabazite) in amygdales, suggesting that the oldest zeolitization predated erosion of the clasts at fault scarps in the basalt. Zeolite minerals in the McCoy Brook Formation sedimentary rocks are restricted to a few discrete zones, including major faults. Massive veins within faults consist principally of chabazite. Rosettes of quartz and either "heulandite" or stellerite appear to have precipitated in situ in the muddy matrix of talus and debris-flow deposits within a few metres of these faults.